A Mirror for the Modern Man: The Siyar Šaʿbiyya as Advice Literature in Tunisian Judeo-Arabic Editions - Schine, Rachel (Arabica, 2018)
Historically, the siyar šaʿbiyya (sing. sīra) corpus—a collection of popular, orally-performed Arabic chivalric legends—have been cast as being outside of the ambit of adab (belles-lettres). Rather, scholars and critics both classical and modern have tended to regard them as tall tales and pseudo-histories. In closing his 1887 Judeo-Arabic edition of Sīrat Sayf b. Ḏī Yazan (Sīrat al-azaliyya), the Tunisian-Jewish litterateur Rabbi Eliezer (Lazarro) Farḥī provides a seven-point list detailing the practical benefits of reading a sīra. In doing so, he opens a different pathway for approaching the text, in the manner of a mirror-for-princes. Examining Farḥī’s framework in its historical context as well as with reference to scholarship on other popular works such as the 1001 Nights and on the nature of adab and wisdom literature, I offer a model for re-envisioning the sīras as principally didactic texts, rather than sources for entertainment. This I do in accordance with the terms of the sīras’ fin-de-siècle publisher, who casts them as a mirror for the modern Jewish man aspiring to keep apace with life in French colonial Tunis. I conclude not only that Farḥī’s approach to the sīra was likely widespread, but that his work testifies to sustained interest among Jewish audiences in the sīras into modern times, making this minority group’s use of these texts integral to the sīras’ diachronic reception history.